2016
DOI: 10.1063/1.4947268
|View full text |Cite
|
Sign up to set email alerts
|

Goos-Hänchen-like shift in biased silicene

Abstract: We have theoretically studied the Goos-Hänchen-like shift of spinor-unpolarized beams tunneling through various gate-biased silicene nanostructures. Following the stationary-phase method, lateral displacement in single-, dual-, and multiple-gated silicene systems has been systematically demonstrated. It is shown for simple single-gated silicene that lateral displacement can be generally enhanced by Fabry-Perot interference, and near the transition point turning on the evanescent mode a very large lateral shift… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…[22,23] It has demonstrated that for a normal/ferromagnetic/normal silicene junction, the GHL shift is negative and positive. [24,25] However, there are few further studies on simultaneous valley-and spin-polarized GHL shift in silicene. Recently, it is reported that the off-resonant circularly polarized light can open a band gap of the Dirac cone in silicene, [26][27][28] which can lead to the valley separation.…”
Section: Introductionmentioning
confidence: 99%
“…[22,23] It has demonstrated that for a normal/ferromagnetic/normal silicene junction, the GHL shift is negative and positive. [24,25] However, there are few further studies on simultaneous valley-and spin-polarized GHL shift in silicene. Recently, it is reported that the off-resonant circularly polarized light can open a band gap of the Dirac cone in silicene, [26][27][28] which can lead to the valley separation.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, various metamaterials such as black phosphorus, silicene, and graphene have been used to increase the efficiency of multifunctional logic gates [27,28]. Special attention has been paid to graphene because it is the most promising candidate when tunability is important [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…During the past five years, the graphene counter parts, including silicene, transitionmetal dichalcogenides (TMDCs), and phosphorene, etc. have been successively syn thesized in experiment, making the study of opticslike phe nomena in 2D materials to be an emerging topic [12][13][14][15]. In contrast to graphene, the TMDCs such as WSe 2 have a strong spin-orbit coupling (SOC) (2λ c = 30 meV for the conduc tion band edge and 2λ v = 450 meV for the valence band edge [16]) originated from the d orbital of the heavy metal atoms [17].…”
Section: Introductionmentioning
confidence: 99%